RE-TREATMENT OF MISMANAGED BILATERAL CONDYLAR FRACTURE AND POST-SURGICAL COMPLICATION - Shuka Oyagi; Nyoman Ayu Anggayanti; Anak Agung Manik Swayoga; Agus Dwi Sastrawan; Eka Marwansyah Oli'i (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: Improper management of condyle fractures can lead to changes in the structure of the temporomandibular joint, which can impact the patient's oral function. Corrective surgery is necessary to restore the patient's function and quality of life. This case report aims to discuss the procedure of bilateral condylectomy in neglected condylar fracture, as well as the risks and post-operative complication management. Case: A 26-year-old female patient presented with mandibular hypomobility and occasional temporomandibular pain. The patient had history of a traffic accident around four months ago, and was managed in a public hospital but symptoms persisted. Case Treatment: After thorough examinations, the patient was diagnosed with neglected complete bilateral condylar fracture with displacement and managed via bilateral condylectomy. Post-operative, the patient presented with anterior open-bite and facial paralysis on the right side, and was treated accordingly. During 4-month follow-up, complications and chief complaints had all subsided. Discussions: Mismanagement of condylar fracture could result in malunion of fragments, which is difficult to reposition due to the changes that have already occurred in the temporomandibular structure. Condylectomy is often necessary to relieve symptoms, although bilateral condylectomy poses certain neurological risks. Prompt recognition and intervention of nerve injury is important to prevent permanent complication. Conclusion and Suggestions: Condylectomy could properly treat neglected bilateral condylar fracture in adult patients. Operators must know the associated risk and management of post-operative complications.